Story incentive: the effect of national stories on voter turnout. Issue 2 (18th May 2021) - Shenhav, Shaul R.; Sheafer, Tamir; Zoizner, Alon; van Hoof, Anita; Kleinnijenhuis, Jan; Kaplan, Yael Rivkah; Hopmann, David Nicolas
Abstract: This article contends that an important driver of turnout is the national stories embraced by citizens. We suggest the notion of 'story incentive, ' whereby adopting a group's story components – those that connect the past, the future, and prominent national characters – motivates individuals to participate in that group's political activities. Leaning on narrative theories and studies on voter turnout, we develop and test hypotheses regarding the effect of story components on the likelihood of voting. Our measurements of story incentives are based on election surveys and encompass Denmark, Israel, the Netherlands, the UK, and the US. The results support the main story-incentive hypothesis. We discuss the theoretical ramifications of the connection between adherence to national stories and voter turnout.